Utilization by finishing pigs of reconstituted sorghum grain treated with enzymes or enzymes plus a bacterial inoculant prior to ensiling - Heidker, J.I.; Behnke, Keith C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred eight finishing pigs averaging 117 lb were used to evaluate the effects of adding enzymes with or without a bacterial inoculant to reconstituted sorghum grain used in swine diets. No differences were noted in gain, feed efficiency, or carcass characteristics as determined by ultrasonic scanning.
Keywords: Swine; Reconstituted; Grain sorghum; Enzymes; Inoculant; Finishing pigs